Development of yeast additives for feeding ruminants in Cuba - Marrero, Yoandra; Galindo, Juana; Castillo, Yamicela; Ruiz, O. (Cuban Journal of Agricultural Science, 2020)
The information obtained in the Institute of Animal Science of Cuba about the effect of additives with viable yeasts for ruminants is presented. Institutions from Mexico, Colombia and Brazil helped to gather all this information. The document is structured as follows: 1) effect of the yeast Saccharomyces cerevisiae L25/7/13 on ruminal fermentation and milk production, 2) isolation, characterization and molecular identification of yeast strains from the ruminal ecosystem under the edaphoclimatic conditions of Cuba, 3) Effect of Levica-25 (Candida tropicalis) strain on ruminal microbial fermentation of animals that consume fibrous diets and 4) Evaluation of factors affecting the use of yeasts as microbial additives for ruminants (strain, culture medium, inclusion level and diet). This review is a valuable contribution, mainly intended for specialists in nutrition biochemistry, who project the use of viable yeasts as activating additives for ruminal fermentation. Key words: ruminal activators, Saccharomyces, Candida, Pichia